Theoretical, Information Processing, and Situational Factors Affecting Attribution Theory Models of Organizational Behavior - Lord, Robert G.; Smith, Jonathan E. (Academy of Management Review, 1983)
Attributional theories used to explain organizational behavior are overly restrictive. Attributional processes may vary with the type of attributional question addressed and with the level of information processing consistent with situational or motivational factors. Several attributional principles are organized into a typology involving type of attributional question and level of information processing. Boundary conditions affecting the use of particular principles are identified and the importance of differences among attributional processes are discussed.